Autonomic neuropathy in systemic sclerosis. Issue 7 (July 1988) - Klimiuk, P S; Taylor, L; Baker, R D; Jayson, M I
Abstract : Autonomic function assessed by tests of cardiovascular reflexes was studied in 25 patients with systemic sclerosis and 10 patients with primary Raynaud's phenomenon. A comparison was made with 13 normal healthy subjects. Significant abnormalities in the cardiovascular reflexes were found in systemic sclerosis, both in the CREST (calcinosis, Raynaud's phenomenon, oesophageal dysmotility, sclerodactyly, telangiectasia) variant and also in those patients with diffuse involvement. There was sympathetic and parasympathetic dysfunction. These findings suggest that autonomic neuropathy is a feature of systemic sclerosis.